High-flow-state and high-strength alkali-activated material and preparation method thereof
By using alkali-excited filling materials prepared by raw materials such as slag powder and phosphogypsum, the problems of insufficient strength and poor fluidity in the early stage were solved, and the consideration of high early strength and high fluidity was achieved, the application scope of phosphogypsum was expanded and the recycling of resources was promoted.
Patent Information
- Application Number
- CN202510127929.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing phosphogypsum base excitation filler materials have problems of insufficient strength and poor high fluidity in the early stage, and are difficult to promote and use on a large scale in actual projects, which is not conducive to the resource utilization of phosphogypsum.
Raw materials such as slag powder, phosphogypsum, fly ash, alkali triggers are used to form polymers with stable three-dimensional network structures through hydration reactions, increasing the crosslinking density, thereby improving the early mechanical strength and fluidity of the material.
On the premise of ensuring liquidity, the early strength of the filling material is significantly improved, the application scope of phosphogypsum is expanded, production costs and environmental pollution are reduced, and resource recycling is promoted.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of civil engineering materials, and in particular to a high-fluidity and high-strength alkali-activated material and a preparation method thereof. Background Art
[0002] Phosphogypsum is a solid waste generated in the wet phosphoric acid process. At present, phosphogypsum is often treated by open-air stacking or nearby landfill, which not only occupies a large amount of land resources, but also has an adverse impact on the natural environment. Therefore, the resource utilization of phosphogypsum has become an urgent problem to be solved in the fields of phosphorus chemical industry and environmental engineering. Considering that phosphogypsum has high activity, it will be used in alkali-activated grouting materials. It can form filling materials with certain strength and fluidity through hydration reaction, and can be used in grouting, repair, reinforcement and other fields of civil engineering structures. It is not only an effective means to realize the reuse of phosphogypsum, but also can replace traditional cement-based grouting materials to a certain extent, alleviating the damage caused by cement production. Emissions and other environmental issues.
[0003] However, an analysis of the current status of existing phosphogypsum-based alkali-activated filling materials revealed that they generally have problems with poor water resistance and insufficient early strength, making it difficult to take into account both early strength and high fluidity at the same time. It is difficult to promote their use on a large scale in actual projects, which is not conducive to the resource reuse of phosphogypsum.
[0004] In view of this, the present invention proposes a high-fluidity and high-early-strength slag-phosphogypsum-based alkali-activated filling material and a preparation method thereof, which, while ensuring the utilization rate of phosphogypsum, takes into account the early strength and high fluidity of the alkali-activated filling material, thereby further improving the application scope of phosphogypsum. Summary of the invention
[0005] The purpose of the present invention is to provide a high-fluidity and high-strength alkali-activated material and a preparation method thereof, so as to solve the problems that the prior art phosphogypsum-based alkali-activated filling materials have insufficient early strength and poor high fluidity, are difficult to promote and use on a large scale in actual projects, and are not conducive to the resource recycling of phosphogypsum.
[0006] To achieve the above-mentioned purpose, the present invention provides a high-fluidity and high-strength alkali-activated material, comprising the following raw materials in parts by weight: 33-39 parts of slag powder, 0.3-0.5 parts of nano-silicon dioxide, 3-6 parts of slaked lime, 15-20 parts of phosphogypsum, 3-4 parts of fly ash, 35-40 parts of alkali-activated solvent, 0.6-1 parts of isopentanol polyoxyethylene ether, 0.4-0.7 parts of acrylic acid, 0.04-0.12 parts of maleic anhydride, 0.1-0.3 parts of ammonium persulfate, and 30-38 parts of water.
[0007] Preferably, the alkali-activated solvent comprises sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2-1.25, and the modulus of sodium silicate is 2.0.
[0008] Preferably, the slag powder is S95 grade slag powder, and the particle size of nano silicon dioxide is not greater than 20 nm.
[0009] Preferably, the phosphogypsum is dehydrated to a moisture content of less than 2%, and passes through a 0.15 mm square hole sieve.
[0010] Preferably, the molecular weight of the isopentanol polyoxyethylene ether is 2000-5000.
[0011] A method for preparing a high-fluidity and high-strength alkali-activated material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, adding phosphogypsum, fly ash, slaked lime and the other half volume of the alkali-activated solvent and stirring for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating, and keeping the temperature for 2-3 hours to obtain a high-fluidity and high-strength alkali-activated material.
[0012] Preferably, in step five, the temperature is raised to 40-60°C.
[0013] The advantages and beneficial effects of the present invention using the above-mentioned high-fluidity and high-strength alkali-activated material and its preparation method are: 1. The present invention forms a polymer with a stable three-dimensional network structure through the reaction of slag powder, phosphogypsum, fly ash, alkali activator, etc., promotes gel formation, and increases its cross-linking density, thereby giving the filling material excellent early mechanical strength while ensuring fluidity.
[0014] 2. The present invention uses slag powder and phosphogypsum as main raw materials to achieve high-dose use of phosphogypsum. By utilizing industrial solid wastes such as phosphogypsum, slag powder, fly ash, etc. as main raw materials, not only the production cost is significantly reduced, but also environmental pollution can be reduced. At the same time, the recycling of resources can be effectively promoted. The prepared phosphogypsum-based alkali-activated material can be used in engineering fields such as construction, roads or bridges, and can replace traditional cement-based materials to a certain extent, reduce carbon emissions and expand market application prospects.
[0015] 3. By adding slaked lime and nano-silicon dioxide, the shortcomings of poor water resistance and weak early activity of phosphogypsum can be improved, so as to achieve the goal of high early strength and high fluidity of alkali-activated filling materials.
[0016] 4. Isoprenol polyoxyethylene ether, acrylic acid, maleic anhydride, and ammonium persulfate have good compatibility with mineral admixtures, and improve the fluidity and early strength of alkali-activated materials.
[0017] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further illustrated by the following examples.
[0019] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0020] Unless otherwise defined, the equipment, reagents and other materials used in the present invention are all commercially available.
[0021] Example 1 A high-fluidity and high-strength alkali-activated material comprises the following raw materials in parts by weight: 33 parts of slag powder, 0.3 parts of nano-silicon dioxide, 5 parts of slaked lime, 15 parts of phosphogypsum, 3 parts of fly ash, 35 parts of alkali-activated solvent, 0.8 parts of isopentanol polyoxyethylene ether, 0.5 parts of acrylic acid, 0.06 parts of maleic anhydride, 0.15 parts of ammonium persulfate, and 32 parts of water.
[0022] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2, and the modulus of sodium silicate is 2.0.
[0023] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0024] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0025] The molecular weight of isopentanol polyoxyethylene ether is 2800.
[0026] A method for preparing a high-fluidity and high-strength alkali-activated material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, adding phosphogypsum, fly ash, slaked lime and the other half volume of the alkali-activated solvent and stirring for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating to 40° C., and keeping the temperature for 2.5 hours to obtain a high-fluidity and high-strength alkali-activated material.
[0027] Example 2 A high-fluidity and high-strength alkali-activated material comprises the following raw materials in parts by weight: 38 parts of slag powder, 0.4 parts of nano-silicon dioxide, 3 parts of slaked lime, 18 parts of phosphogypsum, 3.5 parts of fly ash, 40 parts of alkali-activated solvent, 0.6 parts of isopentanol polyoxyethylene ether, 0.6 parts of acrylic acid, 0.08 parts of maleic anhydride, 0.2 parts of ammonium persulfate, and 35 parts of water.
[0028] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.25, and the modulus of sodium silicate is 2.0.
[0029] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0030] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0031] The molecular weight of isopentanol polyoxyethylene ether is 3500.
[0032] A method for preparing a high-fluidity and high-strength alkali-activated material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, adding phosphogypsum, fly ash, slaked lime and the other half volume of the alkali-activated solvent and stirring for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating to 50° C., and keeping the temperature for 3 hours, thereby obtaining a high-fluidity and high-strength alkali-activated material.
[0033] Example 3 A high-fluidity and high-strength alkali-activated material comprises the following raw materials in parts by weight: 39 parts of slag powder, 0.5 parts of nano-silicon dioxide, 5 parts of slaked lime, 20 parts of phosphogypsum, 4 parts of fly ash, 36 parts of alkali-activated solvent, 0.7 parts of isopentanol polyoxyethylene ether, 0.7 parts of acrylic acid, 0.1 parts of maleic anhydride, 0.20 parts of ammonium persulfate, and 38 parts of water.
[0034] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.25, and the modulus of sodium silicate is 2.0.
[0035] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0036] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0037] The molecular weight of isopentanol polyoxyethylene ether is 4000.
[0038] A method for preparing a high-fluidity and high-strength alkali-activated material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, adding phosphogypsum, fly ash, slaked lime and the other half volume of the alkali-activated solvent and stirring for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating to 60° C., and keeping the temperature for 2 hours, thereby obtaining a high-fluidity and high-strength alkali-activated material.
[0039] Comparative Example 1 An alkali-activated material comprises the following raw materials in parts by weight: 33 parts of slag powder, 0.3 parts of nano-silicon dioxide, 5 parts of slaked lime, 15 parts of phosphogypsum, 3 parts of fly ash, 35 parts of alkali-activated solvent, and 32 parts of water.
[0040] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2, and the modulus of sodium silicate is 2.0.
[0041] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0042] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0043] A method for preparing an alkali-excited material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3: add phosphogypsum, fly ash, slaked lime and the other half volume of the alkali-activated solvent and stir for 2 minutes; thus, the alkali-activated material is obtained.
[0044] Comparative Example 2 An alkali-activated material comprises the following raw materials in parts by weight: 33 parts of slag powder, 15 parts of phosphogypsum, 3 parts of fly ash, 35 parts of alkali-activated solvent, 0.8 parts of isopentanol polyoxyethylene ether, 0.5 parts of acrylic acid, 0.06 parts of maleic anhydride, 0.15 parts of ammonium persulfate, and 32 parts of water.
[0045] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2, and the modulus of sodium silicate is 2.0.
[0046] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0047] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0048] The molecular weight of isopentanol polyoxyethylene ether is 2800.
[0049] A method for preparing an alkali-excited material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, adding phosphogypsum, fly ash and the other half volume of alkali-activated solvent and stirring for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating to 40-60° C., and keeping the temperature for 2-3 hours to obtain the alkali-activated material.
[0050] Comparative Example 3 An alkali-activated material comprises the following raw materials in parts by weight: 33 parts of slag powder, 15 parts of phosphogypsum, 3 parts of fly ash, 35 parts of alkali-activated solvent, and 32 parts of water.
[0051] The alkali-activated solvent includes sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2, and the modulus of sodium silicate is 2.0.
[0052] The slag powder adopts S95 grade slag powder, and the particle size of nano silicon dioxide is not more than 20nm.
[0053] The phosphogypsum is dehydrated to a moisture content of less than 2% and passed through a 0.15mm square hole sieve.
[0054] A method for preparing an alkali-excited material comprises the following steps: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3: add phosphogypsum, fly ash and the other half volume of alkali-activated solvent and stir for 2 minutes to obtain alkali-activated material.
[0055] The alkali-activated materials provided in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1. The flow time is usually used to evaluate the fluidity of the grouting material, the 3-day compressive strength and flexural strength are used to evaluate the early strength of the grouting material, and the 7-day compressive strength and flexural strength are used to evaluate the overall mechanical properties of the grouting material. The flow time must be within the specified range, and the smaller it is, the higher the fluidity; the greater the 3-day and 7-day compressive strength and flexural strength, the better.
[0056] Table 1 Performance test data ;
[0057] By comparing Examples 1-3 with Comparative Examples 1-3, it is shown that the slaked lime and nano-silicon dioxide in the present invention improve the poor water resistance and weak early activity of phosphogypsum, and achieve the purpose of high early strength and high fluidity of alkali-activated filling materials. Isoprenol polyoxyethylene ether, acrylic acid, maleic anhydride, and ammonium persulfate have good compatibility with mineral admixtures, and improve the fluidity and early strength of alkali-activated materials.
[0058] Therefore, the present invention adopts the above-mentioned high-fluidity and high-strength alkali-activated material and its preparation method, which solves the problem that the existing phosphogypsum-based alkali-activated filling materials have insufficient early strength and poor high fluidity, are difficult to promote and use on a large scale in actual projects, and are not conducive to the resource recycling of phosphogypsum.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A high-fluidity and high-strength alkali-activated material, characterized in that: The invention comprises the following raw materials in parts by weight: 33-39 parts of slag powder, 0.3-0.5 parts of nano silicon dioxide, 3-6 parts of slaked lime, 15-20 parts of phosphogypsum, 3-4 parts of fly ash, 35-40 parts of alkali-activated solvent, 0.6-1 parts of isopentanol polyoxyethylene ether, 0.4-0.7 parts of acrylic acid, 0.04-0.12 parts of maleic anhydride, 0.1-0.3 parts of ammonium persulfate and 30-38 parts of water.
2. The high-fluidity and high-strength alkali-activated material according to claim 1, characterized in that: The alkali-activated solvent comprises sodium hydroxide and sodium silicate, the mass ratio of sodium silicate to sodium hydroxide is 1.2-1.25, and the modulus of sodium silicate is 2.
0.
3. The high-fluidity and high-strength alkali-activated material according to claim 1, characterized in that: The slag powder is S95 grade slag powder, and the particle size of nano silicon dioxide is not greater than 20nm.
4. The high-fluidity and high-strength alkali-activated material according to claim 1, characterized in that: The phosphogypsum is dehydrated to a moisture content of less than 2%, and passes through a 0.15 mm square hole sieve.
5. The high-fluidity and high-strength alkali-activated material according to claim 1, characterized in that: The molecular weight of the isopentanol polyoxyethylene ether is 2000-5000.
6. A method for preparing a high-fluidity and high-strength alkali-activated material according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: prepare an alkali-activated solvent, mix water and sodium silicate, and gradually add sodium hydroxide while stirring with a magnetic suction until the pH of the solution is greater than 13; Step 2: Mix the slag powder and nano-silicon dioxide with half of the alkali-activated solvent in step 1 and stir for 1 minute; Step 3, add phosphogypsum, fly ash, slaked lime and the other half volume of alkali-activated solvent, and stir for 2 minutes; Step 4, dissolving the isopentanol polyoxyethylene ether in water, adding acrylic acid and maleic anhydride and mixing evenly to obtain a mixed solution, and preparing an aqueous solution of ammonium persulfate and adding the aqueous solution dropwise to the mixed solution; Step 5, adding the mixed solution of step 4 to the mixed solution of step 3, stirring and heating, and keeping the temperature for 2-3 hours to obtain a high-fluidity and high-strength alkali-activated material.
7. The method for preparing a high-fluidity and high-strength alkali-activated material according to claim 6, characterized in that: In step five, the temperature is raised to 40-60°C.
Citation Information
Patent Citations
Preparation method of quick setting and rapid hardening gangue alkali-activated rapid repairing material
CN109942238A
Special alkali-activated concrete material for underwater pouring
CN110041036A
Green alkali-activated material for repair and protection and preparation method thereof
CN112521115A
Polycarboxylic acid water reducing agent containing maleic anhydride and preparation method thereof
CN113214438A
Phosphogypsum-based geopolymer and preparation method thereof
CN115159874A